Implementasi Laboratorium Mini Kitchen Sebagai Media Pembelajaran Berbasis Teaching Factory di SMK Suarna Wisata Banyuwangi - Kanom, Kanom; Ari Perdana, Muhamad; Febrian, Ayu Wanda; Rachma Amalia, Firda (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2023)
Suarna Wisata Blimbingsari Vocational School is a Vocational High School that prioritizes practice rather than theory. To be declared competent to become a waiter and/or demi chef, students are required to be able to understand each function of food and beverage equipment. The existence of a laboratory as a learning medium is considered important, especially in supporting teaching factory-based learning (TEFA). The infrastructure standards for the Catering Skills Study Program for the Catering Services Competency Competency must at least have a food processing practice laboratory and a restaurant service practice laboratory. Each laboratory is equipped with practical equipment in accordance with the needs of students in each study group. The provision of a mini kitchen laboratory was chosen as an effort to present Food and Beverage practicum classes starting from FNB Products, introduction to equipment, table set up, sequence of service, to serving procedures to consumers. It is felt that this will be superior and relevant for tefa-based vocational school learning conditions.